Education On A Health Administration Model Based On Early Detection And Referral For Children With Disabilities In Early Childhood - Siti Masdah; Nita Putriasti Mayarestya; Raditya Rahmatun Nur Hidayat; Wiranda Albarenzi; Shodikin Shodikin; Imroatun Nisa (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Raudhatul Athfal (RA) teachers play a strategic role in the early detection of developmental disorders in children; however, many still have limited competence in developmental screening, school health administration, and referral procedures. This community service program aimed to improve teachers' knowledge and skills through a health administration model based on early detection and referral for children with disabilities. The program was conducted on May 1, 2026, at TK Al-Hasani, West Pontianak, involving 20 participants consisting of 17 RA teachers, 1 educational staff member, and 2 parents/guardians. The intervention included interactive lectures, hands-on training, developmental screening simulations, communication and referral role-play, and participatory mentoring through individual guidance in completing developmental observation forms, school health administration records, and referral documents. Program effectiveness was evaluated using a one-group pretest-posttest design. The results demonstrated improvements across all knowledge indicators: knowledge of early disability detection increased from 78.4 to 84.7 (6.3-point increase), understanding of developmental delay signs from 70.1 to 86.5 (16.4-point increase), understanding of the referral system from 65.8 to 82.9 (17.1-point increase), and understanding of school health administration from 72.3 to 81.6 (9.3-point increase). In addition, all participants successfully practiced completing health administration forms and referral documents during the supervised simulation sessions. The novelty of this program lies in integrating education, hands-on practice, intensive mentoring, and the provision of practical school health administration tools, making it more comprehensive than conventional training that focuses solely on knowledge enhancement. This model has the potential to strengthen the sustainable implementation of early detection and referral systems in early childhood education settings